PROVERBS AND SAYINGS AS PAREMIOLOGICAL UNITS (ResearchJet Journal of Analysis and Inventions, 2021)
This article investigates different researches and contributions which were done by language experts in order to elaborate paremiological units. It explains the most important functions of proverbs and sayings. This article gives rich basis for developing proverbs and sayings as paremiological units. One of the main factors that boosts the effectiveness of speech is the effective use of the paremological units (phraseologism, prose, dialect) in the language.